Global Energy Scenarios Meeting Stringent Climate Targets: A comparison between the Global Energy System Model GET 1.0 and the Regionalised Model GET-R 1.0., Thesis for Master of Science in Physics with an emphasis on Problem Solving. - Grahn, Maria (My University, 2002)
The greenhouse effect is considered to be one of the most serious global hazards to the environment and the "Kyoto Agreement" stipulates that emissions of greenhouse gases must be reduced. Reduction of CO2 emissions involves considerable changes in present energy systems. In year 2000 the Department of Physical Resource Theory (PhRT) at Chalmers University of Technology developed a global energy system model, designed to analyse the world's energy use to the year 2100. In a regionalisation process, this study has divided the world into eleven geographical areas and then applied these to the original PhRT model. With the purpose of gaining a better understanding of the global energy system, a comparison is made between the PhRT Model (GET 1.0) and the Regionalised Model (GET-R 1.0). Both models are linear programmed and have three end-use sectors; electricity, heat and transport fuel. They are devised to meet exogenous energy demands at the lowest global energy system cost. To minimise these costs, interregional trade is permitted, and the model places an upper limit on CO2 emissions, so as to stabilise the atmospheric CO2 content at 400 ppm. Both models show the same overall pattern. The transportation sector shows a transition from petroleum fuels in internal combustion engines towards hydrogen fuel cell engines, in the middle of the century. The major difference is that fuel cell technologies are introduced one decade earlier, in the regionalised model. Within the electricity production sector the oil is phased out early and both coal (with CO2-sequestration) and solar produced hydrogen, increase toward the middle of the century. Biomass is the dominant fuel in the heat production sector and a large trade of biomass occurs to minimise the global costs. It is concluded that it is technically and economically possible to meet stringent CO2 constraints (400 ppm) in combination with a rapid increase in energy demand.
Keywords: Optimeringslära, systemteori; Teknik och social förändring; Optimization, systems theory; Technology and social change